The effect of asparaginase therapy on methotrexate toxicity and efficacy in children with acute lymphoblastic leukemia. Issue 12 (15th October 2019) - Kloos, Robin Q. H.; Pieters, Rob; van den Bos, Cor; van Eijkelenburg, Natasha K. A.; de Jonge, Robert; van der Sluis, Inge M.
Abstract: Asparaginase and methotrexate (MTX), both essential for pediatric acute lymphoblastic leukemia therapy, are often used concomitantly. Depending on the sequence, in vitro, asparaginase inhibits MTX-polyglutamate (MTXPG) formation, and side effects overlap. MTX toxicity and efficacy, reflected by intracellular erythrocyte MTXPG's, were compared between children treated with and without asparaginase during high dose MTX (HD-MTX) courses of the DCOG ALL-11 protocol (NL50250.078.14). Seventy-three patients, of whom 23 received asparaginase during the HD-MTX courses, were included. Grade 3–4 leukopenia and neutropenia occurred more often (59% and 86% vs. 30% and 62%). The number of infections, grade 3–4 hepatotoxicity, nephrotoxicity, and neurotoxicity did not differ. Patients with asparaginase had lower MTXPG levels, although to a lesser extent than in vitro studies. Although patients with asparaginase during HD-MTX courses showed more myelosuppression, this had no (serious) clinical consequences. Regarding the MTX efficacy, the schedule-related antagonism seen in in vitro seems less important in vivo .